2020
DOI: 10.1103/physrevb.102.104112
|View full text |Cite
|
Sign up to set email alerts
|

Phonon dispersion throughout the iron spin crossover in ferropericlase

Abstract: Ferropericlase (Fp), (Mg1-xFex)O, is the second most abundant phase in the Earth's lower mantle.At relevant pressure-temperature conditions, iron in Fp undergoes a high spin (HS), S=2, to low spin (LS), S=0, state change. The nature of this phenomenon is quite well understood now, but there are still basic questions regarding the structural stability and the existence of soft phonon modes during this iron state change. General theories exist to explain the volume reduction, the significant thermo-elastic anoma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 54 publications
2
9
0
Order By: Relevance
“…No imaginary frequency is found in either HS or LS state up to 100 GPa. This is consistent with the recent phonon calculations in x F e =0.0625 fp with density functional perturbation theory [29]. Therefore, both HS and LS states of fp with iron concentrations lower than 0.1875 are dynamically stable.…”
Section: Finite Temperature Effect On the Spin Crossoversupporting
confidence: 92%
See 2 more Smart Citations
“…No imaginary frequency is found in either HS or LS state up to 100 GPa. This is consistent with the recent phonon calculations in x F e =0.0625 fp with density functional perturbation theory [29]. Therefore, both HS and LS states of fp with iron concentrations lower than 0.1875 are dynamically stable.…”
Section: Finite Temperature Effect On the Spin Crossoversupporting
confidence: 92%
“…Because fp is a solid solution of FeO and MgO, a uniform distribution is more relevant to the real situation. Moreover, it has been shown that different types of Fe configurations have only a small effect on the spin crossover [29]. With x F e =0.1875, one would expect the exchange interaction between Fe ions in the HS state to be sizable because of the small Fe-Fe distance.…”
Section: Spin Crossover Of Fp18 At T=0kmentioning
confidence: 99%
See 1 more Smart Citation
“…We further investigate the B1-LS → B2-IS transition in fp with larger iron concentrations in Fe 2 Mg 30 O 32 and Fe 4 Mg 28 O 32 (x F e = 0.0625 and 0.125, noted as fp6 and fp12 hereafter). It has been shown that the iron arrangement in the fp solid solution has a minor effect on the spin state change pressure in the B1 phase, at least for small x F e as investigated here [44]. Therefore, we distribute Fe uniformly in both B1 and B2 lattices and disregard Fe-Fe interaction effects in first-order (see Supplementary Fig.…”
Section: B1-b2 Phase Boundary Up To Xf E= 0125mentioning
confidence: 99%
“…The present model allows for an isostructural phase transition at low temperature, as well as a crossover: such a true phase transition, an associated critical point, would require a coupling J between sites which disfavoured mixing. This coupling may come from short ranged strain [41,42], magnetic spin coupling or from phonons [71], or be calculated directly from first principles [70], and may vary with pressure [72]. Magnetowüstite (Mg,Fe)O and perovskite (Mg,Fe)SiO 3 in the iron rich regime are prime candidates.…”
Section: Non-ideal Solution Solid Modelmentioning
confidence: 99%